Labour, Liberalism, and the Democratic Party: A Vexed Alliance - Lichtenstein, Nelson (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2011)
This essay argues that the American trade union movement constitutes a social democratic bloc within the U.S. body politic, episodically successful in broadening the welfare state, expanding citizenship rights, and defending the standard of living of working class Americans, including those unlikely to be found on the union membership roll. But such political influence, which has also helped make organized labour a backbone of Democratic Party electoral mobilization, has rarely been of usefulness when the unions sought to enhance their own institutional vibrancy, their own capacity to organize new members. When demands of this sort are put forward, Republican presidents and politicians denounce them outright, while most Democrats, including virtually every postwar president from that party, see such legislation as but the product of an unpopular interest group and thus safely devalued and ignored.American unions have almost always failed to win legislation advancing their institutional strength and political legitimacy. To understand why, this essay explores the three distinct regimes which have governed trade union “bargaining,” with employers, with the Democrats, and with the state, during the era since the New Deal. They are the era of the New Deal itself (1933-1947) during which a corporatist politicialization of all wage, price and production issues achieved some purchase; the years of classic industrial pluralism and collective bargaining (1947-1980), in which industrial relations was reprivatized to a large extent; and finally, our current moment (1980s forward) in which the labour movement exists and holds the possibility of growth largely in government and the service sector. A highly politicized form of tripartite bargaining, between companies, unions, and government (mainly state and local), has provided the chief avenue for raising the social wage and building nodes of trade union influence in key government-dependent sectors of the economy. With the arrival of the Obama era, this third system is becoming the only game in town, although this appears to be falling far short of labourite expectations.